Case reportIntraluminal urethral brachytherapy for recurrence of transitional cell carcinoma of urinary bladder in urethral stump - Chakrabarti, Bikramjit; Ghorai, Suman; Ray, Somapriya Basu; Kar, Sanjay Kumar (Journal of Contemporary Brachytherapy, 2013)
We report a unique case of successfully performed intraluminal brachytherapy for low volume urethral mucosal recurrence of transitional cell carcinoma urinary bladder, initially treated by transurethral resection of bladder tumor, followed by radical cystectomy. Since the patient was unwilling to undergo any other operational interventions, intraluminal brachytherapy of urethra was attempted. Fluroscopy guided intraluminal HDR brachytherapy using Lumencath ® catheter under local anesthesia, and remote afterloading system (Nucletron, an Elekta company, Elekta AB, Stockholm, Sweden) was performed. A fraction dose of 7 Gy in seven weekly fractions was prescribed at 0.5 cm from the single applicator. The result was promising in terms of local control and symptomatic relief. Therefore, intraluminal brachytherapy in low volume superficial local disease in urethra may play a potential role, and should be applied when repeated surgery is not feasible due to technical or medical reasons.